A direct approach for modeling ion-exchange residual stress distribution in glass. (August 2014) - Ma, Lifeng; Sun, Kun
In this article, we propose a direct approach to model the residual stress in glass due to ion exchange. Rather than employing the traditional thermal strain analogy approach in literature, the nominal residual strain distribution due to ion exchange is addressed with direct analysis of ion-exchange volume change first. Then, based on the principle of superposition, the residual stress in ion-exchanged glass is then formulated with a direct approach in the framework of elasticity, and a complete solution for residual stress distribution is obtained with consideration of the asymmetric ion molar concentration distribution. Finally, a simple example is provided to demonstrate the validity of the fundamental formulations proposed in this article.